Understanding change in disruptive contexts: The role of the time paradox and locus of control - Manisalıgil, Alperen; Gölgeci, İsmail; Bakker, Arnold B.; Aysan, Ahmet Faruk; Babacan, Mehmet; Gür, Nurullah (Elsevier Inc., 2023)
We examine how the experience of time and locus of control influence organizational change in disruptive contexts. Through the cycles of the COVID-19 pandemic restrictions and their relaxations in Turkey, we found that organizations approached change similarly in the short term but differently in the long term. To unpack the mechanism behind these observations, we analyzed in-depth qualitative data from five organizations from March 2020 to September 2021. We reveal that the change process creates time pressure in disruptive contexts, and a time paradox emerges to the extent that the change outcomes increase the available time under time pressure. Depending on their locus of control, individuals either complement organizational change or resist it even more after triggering events that signal the lastingness of the post-disruption situation. Our framework may enhance organizational resilience to future disruptions by highlighting the requirement for change recipients to make complementary moves to regain control.
Keywords: Change; COVID-19; Disruptive Context; Extreme Event; Locus of Control; Time